2020
DOI: 10.1371/journal.pbio.3000629
|View full text |Cite
|
Sign up to set email alerts
|

The unidentified hormonal defense against weight gain

Abstract: Human biology has evolved to keep body fat within a range that supports survival. During the last 25 years, obesity biologists have uncovered key aspects of physiology that prevent fat mass from becoming too low. In contrast, the mechanisms that counteract excessive adipose expansion are largely unknown. Evidence dating back to the 1950s suggests the existence of a blood-borne molecule that defends against weight gain. In this article, we discuss the research supporting an "unidentified factor of overfeeding" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 85 publications
(145 reference statements)
1
32
0
Order By: Relevance
“…At 16-17 weeks of age, Titan mice showed multifocal fatty cells in the pancreas, usually termed pancreatic lipomatosis or steatosis, without atrophic or inflammatory changes of the adjacent parenchyma, a phenotype not present in control mice (Figure 2G). We also found that the average levels of leptin, a hormone secreted by adipocytes( 3 , 5 , 19 ) and known to modulate food intake and fat storage ( 3 , 5 , 19 ), were significantly higher (more than 5-fold; P < 0.001) in 16-17-week-old Titan mice compared to control mice (Figure 2H). Finally, we investigated whether the plasma concentration of fibroblast growth factor 21 (FGF21), a factor associated with MetS in humans ( 20 , 21 ), was altered in Titan mice.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…At 16-17 weeks of age, Titan mice showed multifocal fatty cells in the pancreas, usually termed pancreatic lipomatosis or steatosis, without atrophic or inflammatory changes of the adjacent parenchyma, a phenotype not present in control mice (Figure 2G). We also found that the average levels of leptin, a hormone secreted by adipocytes( 3 , 5 , 19 ) and known to modulate food intake and fat storage ( 3 , 5 , 19 ), were significantly higher (more than 5-fold; P < 0.001) in 16-17-week-old Titan mice compared to control mice (Figure 2H). Finally, we investigated whether the plasma concentration of fibroblast growth factor 21 (FGF21), a factor associated with MetS in humans ( 20 , 21 ), was altered in Titan mice.…”
Section: Resultsmentioning
confidence: 68%
“…Consistent with the notion that hyperlipidemia usually occurs in the presence of insulin resistance, insulin levels were more than 3-fold higher in ad libitum 16-17-week-old Titan mice (Figure S1D). We also measured average levels of leptin, a hormone secreted by adipocytes and known to modulate food intake and fat storage [16][17][18] . Leptin levels were significantly higher (more than 5-fold; P < 0.001) in 16-17-week-old Titan mice compared to control mice (Figure S1E).…”
Section: Hallmarks Of Detrimental Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…122,123 This contention is further emphasized by evidence that protection against weight gain involves unidentified blood-borne factors. 124,125 A nonleptin system (and so far unidentified adipostatic signals) has recently been implicated in the compensatory hypophagia that plays a critical role in the recovery from rapid weight gain induced by overfeeding. 126 On the other hand, the notion of a feedback loop between FFM deficit and compensatory hyperphagia (Figure 9), as suggested by the MSE reanalysis 63 and by recent studies of weight regain after caloric restriction in humans [98][99][100][101][102] and in mice, 127…”
Section: Adipostats and Proteinstats Awaiting Discoverymentioning
confidence: 99%
“…Furthermore, circulating leptin alone does not explain all the findings of parabiotic experiments that have been crucial in the demonstrations that circulating factors are involved in the long‐term control of food intake and weight regulation 122,123 . This contention is further emphasized by evidence that protection against weight gain involves unidentified blood‐borne factors 124,125 . A nonleptin system (and so far unidentified adipostatic signals) has recently been implicated in the compensatory hypophagia that plays a critical role in the recovery from rapid weight gain induced by overfeeding 126 .…”
Section: Implications and New Perspectives For Cachexia And Obesity Rmentioning
confidence: 99%